Pre-Coding in Early Childhood Education: Equipping Teachers for the Digital Age - Utami, Amaira; Nurismawati, Riana; Husna, Hanna Nurul; Rusmana, Ai Nurlaelasari; Dhitareka, Putra Habib (Jurnal Mandala Pengabdian Masyarakat, 2025)
In the digital world, technology is an important part of human life, driving demand for technology-literate human resources. As technology becomes an integral part of human life, introducing it to young children will benefit them. One approach is to bring the pre-coding concept into the classroom. This community service was held in Bandung, West Java, in partnership with Sekolah Karakter RA SBB Hidayatul Musthafa. The workshop consisted of three stages: an initial phase including socialization, a workshop day, and an evaluation phase. In the main phase, the workshop discussed the need to introduce pre-coding to preschool students, followed by the installation of Gcompris software. In the second session, the teachers are assisted in using Code.org and Scratch Jr as tools to introduce pre-coding concepts to preschool students. At the end, teachers’ interest and self-efficacy regarding teaching the pre-coding concept to early childhood students were assessed. The data indicate that teachers’ interest and self-efficacy are moderate. Therefore, it can be concluded that future training and workshops related to pre-coding will be highly valuable for early childhood teachers.